Transgenic animals as bioreactors: Review - Bősze, Zsuzsanna; Tóth, Sz. (Acta Agraria Kaposváriensis, 1999)
Different systems are being studied and used to prepare recombinant proteins for pharmaceutical use. The blood, and even more so the milk, of transgenic livestock animals appear a very attractive source of pharmaceuticals. The cells from these animals are expected to produce well-matured proteins in potentially huge amounts. The development of recombinant DNA technology coupled with the techniques of microinjection and embryo transfer to introduce foreign genes into the germline of animals has provided the basic tools. Cloning of milk proteins in the late 70s and early 80s, followed by the identification and characterisation of promoter and regulatory sequences of milk protein genes, revealed sufficient genetic information to target genes exclusively to mammary tissue and to respond to hormonal signals. In sheep more than 50% of the protein in milk can be encoded by the transgene without compromising the animal’s health or reproductivity. However, the most natural use of this technology must include modifying the protein content of milk by manipulating the milk protein genes themselves. We have developed a chimeric gene to increase kappa-casein content in transgenic mice and rabbits and to examine its effect on the physicochemical properties of milk As we approach the end of the 1990s the prospect of achieving the aim of producing pharmaceuticals in transgenic farm animals is becoming reality: the first human products are on their way through clinical trials.